Efficiency of silver nano particles in removing Escherichia coli ATCC 25922 from drinking water distribution pipes - Zena H. Ali; Alaa H. Al-Fatlawi (Results in Engineering, 2023)
Many types of pathogenic microorganisms can live and transmitted in water, causing serious health problems upon consumption. So, the current study aimed to design a water distribution system (WDS), parts of it (polyvinyl chloride pipes) were coated with the biologically prepared silver nanoparticles (AgNPs) (green method) using leaves extract of Azadirachta indica (Meliaceae), silver nanoparticles (AgNPs) characterized by UV–Vis spectrum, FTIR spectrum, XRD, FESEM and TEM, also PVC coated with AgNPs pipes were characterized by XRD and FESEM, These techniques demonstrated the successful formation of AgNPs and highly efficient attachment of these nanoparticles to the inner surface of the pipes. To eradicate the viability cells of E. coli ATCC 25922 a laboratory scale water distribution system was built to serve this study, two concentrations of AgNPs (125 and 250) ppm and six exposure times were applied (0.0, 2, 5, 10, 15, and 20) min. to assess the viability rate of water transmitted E. coli ATCC 25922 by pour plate method. The results showed that, the inhibition rate reached 100% at 125 ppm of AgNPs through the period of time15 and 20 min, while with the concentration 250 ppm the inhibition rate reached 100% during period of time10, 15 and 20 min with significant differences between concentrations and exposure time.